Properties and dynamics of meron topological spin textures in the two-dimensional magnet CrCl3 - Mathias Augustin (Nature Portfolio, 2021)
Merons are a type of topological spin texture, with relevance for both fundamental and technological problems. In this theoretical work, Augustin et al. show that the van der Waals ferromagnetic CrCl3 can host merons and anti-merons, and explore the dynamics and interactions of these quasi-particles.